Analisis Perilaku Bullying Verbal Pada Siswa SMPN 01 Pasemah Air Keruh Kabupaten Empat Lawang : Analisis Perilaku Bullying Verbal pada Siswa SMPN 01 Pasemah Air Keruh Kabupaten Empat Lawang - Samsudin; M. Ilham Gilang; Refti Sapitri (DAWUH : Islamic Communication Journal, 2025)
Bullying is an act or behavior that is carried out by hurting Dallam physically, verbally, or emotionally/psychologically by a person or group who feels physically or mentally weaker repeatedly without any resistance with the aim of making the victim suffer. Bullying behavior at SMPN 01 Pasemah Air Keruh, Empat Lawang Regency can create an environment that is less supportive of children's development, both physically and mentally. The bullying behavior that occurred at SMPN 01 Pasemah Air Keruh, Empat Lawang Regency was in the form of physical, verbal and mental. This bullying arises due to misunderstandings and minor problems that have an impact on the victim's mental health. This study aims to: (1) find out the form of verbal bullying behavior in students of SMPN 01 Pasemah Air Keruh, Empat Lawang Regency, (2) find out the impact of verbal bullying behavior on students of SMPN 01 Pasemah Air Keruh, Empat Lawang Regency. The approach used in this study is qualitative with the type of case study research. To find the researcher's data, use interview, observation, and documentation techniques. The data analysis technique is an interactive analysis with stages consisting of data reduction, data presentation, and conclusion drawn. From the research, it was found that (1) the form of verbal bullying behavior that occurred at SMPN 01 Pasemah Air Keruh was insulting, cursing, accusing, and slandering. Meanwhile, the physical bullying that occurs is hitting, pushing, and grabbing/pulling. And the mental bullying that occurs is ostracizing, threatening, and glaring/looking cynically, (2) the impact of bullying behavior, namely the victim of bullying becomes quiet, weak, afraid when meeting with the perpetrator, tired of the perpetrator's treatment of him, becomes very depressed, and also not enthusiastic about learning.